STUDY OF SPORT TALENT IN MALE STUDENTS OF CLASS VII SMP NEGERI 2 JATEN - Muh Arif Dwi Saputro; Sunardi Sunardi; Ahmad Septiandika Adirahma (PHEDHERAL, 2021)
The purpose of this study was to determine the sporting talent in male students of class VII SMP Negeri 2 Jaten the academic year 2019/2020. This research uses a descriptive method. This study wanted to describe giftedness in male students of class VII SMP Negeri 2 Jaten. The population and sample in this study were male students of class VII SMP Negeri 2 Jaten in the academic year 2019/2020. The subjects in this study were male students of grade VII SMP Negeri 2 Jaten in the academic year 2019/2020 as many as 100 students. Data collection techniques in this study used tests and measurements of the sports search model which consisted of 10 test items, namely: height, sitting height, body weight, length of the two arms, throwing a tennis ball, throwing basketball, jumping upright, running agility. , sprint 40 meters and run multi-stage. The data analysis technique used computer software "sport search" and modified sport search. The results of this study show that the sports talents possessed by male students in grade VII of SMP Negeri 2 Jaten for the 2019/2020 academic year which consisted of several sports groups, namely, 37 students (37.00%) of sprint, long running, 5 students (5.00%), throwing a javelin as much as 1 student (1.00%), throwing bullets by 1 student (1.00%), pole jumping by 1 student (1.00%), long jump and multiply 7 students (7.00%), high jumping as many as 31 students (31.00%), archery by 2 students (2.00%), gymnastics as many as 15 students (15.00%). Team / Ball: soccer as many as 32 students (32.00%), futsal as many as 1 student (1.00%), volleyball as many as 44 students (44.00%), handball as many as 23 students (23.00%) . Combative: karate as many as 26 students (26.00%), taekwondo as many as 23 students (23.00%), pencak silat as many as 51 students (51.00%). Racket / Stick: The conclusion of this study is that from a total of 100 students who took the giftedness test sport search, the classification of giftedness level was determined. There were 2 students who were talented to become athletes, 16 students were talented enough to become athletes, 44 students were less talented to become athletes and 38 students were not gifted as athletes.